Higher Education in Bulgaria – A Deterrent for “Brain Drain” from the Country - Dimitrov, Atanas (Research Papers, 2021)
This publication examines existing gaps and shortcomings in the higher education system in Bulgaria that contribute to the "brain drain". The article analyzes publicly available documents, data and other primary and secondary sources. It suggests measures to improve the quality of the higher education system with the aim of attracting prospect students, both national and international, which could serve as a brain-drain deterrent. The paper argues that university curricula should reflect not only the interests of business, but the national and international context and the needs of society as well.
Keywords: Brain drain; Emigration; Integrity; Higher education; Ethics